A developer's guide to the semantic web - Yu, Liyang (Heidelberg : Springer, 2014)
The Semantic Web represents a vision for how to make the huge amount of information on the Web automatically processable by machines on a large scale. For this purpose, a whole suite of standards, technologies and related tools have been specified and developed over the last couple of years, and they have now become the foundation for numerous new applications. A Developer's Guide to the Semantic Web helps the reader to learn the core standards, key components, and underlying concepts. It provides in-depth coverage of both the what-is and how-to aspects of the Semantic Web. From Yu's presentation, the reader will obtain not only a solid understanding about the Semantic Web, but also learn how to combine all the pieces to build new applications on the Semantic Web.
1. A Web of data : toward the idea of the Semantic Web -- 2. The building block for the Semantic Web : RDF -- 3. Other RDF-related technologies : microformats, RDFa, and GRDDL -- 4. RDFS and ontology -- 5. OWL : Web ontology language -- 6. SPARQL : querying the Semantic Web -- 7. FOAF : Friend of a Friend -- 8. DBpedia -- 9. Linked open data -- 10. schema.org and Semantic Markup -- 11. Social networks and the Semantic Web -- 12. Other recent applications : data.gov and Wikidata -- 13. Getting started : change your data intro structured data -- 14. Building the foundation for development on the Semantic Web -- 15. Example : using Jena for development on the Semantic Web -- 16. Follow your nose : a basic Semantic Web agent -- 17. A search engine that supports Rich Snippets -- 18. More application examples on the Semantic Web.
Includes bibliographical references and index.
Keywords: Semantic Web; Web site development; Information storage and retrieval systems